Postharvest Storage of 'Ponkan', 'Satsuma Okitusu' and 'Fremont' Tangerines and Their Minimally Processed Products Using Refrigeration and Controlled Atmosphere - Santos, L. O. [UNESP]; Durigan, J. F. [UNESP]; Martins, R. N. [UNESP]; Durigan, M. F. B. [UNESP]; Stuchi, E. S. (Int Soc Horticultural Science, 2012)
This study aimed to evaluate the postharvest conservation of tangerines 'Fremont', 'Satsuma Okitsu' and 'Ponkan' when stored at different conditions, as well as the quality of the minimally processed product. Fruit were harvested when a sugar: acid ratio of 10.0 to 12.0 for 'S. Okitsu' and 'Fremont' and 16.0 to 19.0 for 'Ponkan' was reached, selected for uniformity of color, size, and absence of injuries. Whole fruits were stored at 3 degrees C, 85% RH and 7 degrees C, 95% RH, and after each storage period, fruits were brought to ambient conditions (22 degrees C, 65% RH) for 3 days before evaluation. The minimally processed products (peeled) were packed in polystyrene trays (22.4x14.8x3.7 cm) coated with polyvinyl chloride (PVC) stretchable, with 0.014 mm thickness, and in lidded packages (500 ml) of transparent polyethylene terephthalate. Fruit were analyzed for appearance, weight loss, respiratory rate, package atmosphere, rind and pulp color, soluble solids, titratable acidity and ascorbic acid content. Shelf life of tangerine 'Fremont' was limited to 42 days based on freshness. Its minimally processed product had a 9 day shelf-life for products packaged in PVC film. The mandarins 'S. Okitsu' had 35 days shelf-life at 7 degrees C, which was reduced to 28 days at 3 degrees C. Its fresh-cut product had a shelf-life of 15 days, stored in PVC or PET. 'Ponkan' fruit stored at 3 degrees C had a shelf life of 35 days, which was reduced to 28 days at 7 degrees C. When minimally processed, its shelf-life lasted for 15 days, whether packaged in PVC or PET. The 'Ponkan' had a shelf-life of 35 days at 3 degrees C and 28 days at 7 degrees C, also limited by loss of freshness. When minimally processed and stored in PVC or PET, its shelf life reached 15 days.
Keywords: Citrus reticulata; Fresh-cut; Cold storage; mandarin